THE ROLES OF PARENTAL ATTACHMENT ON THE PSYCHOLOGICAL WELL-BEING OF ISLAMIC BOARDING SCHOOL STUDENTS - Cahyani, Nabilah; Anindhita, Vidya; Abidin, Fitri Ariyanti (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Adolescent psychological well-being has emerged as a global concern. This cross-sectional study investigates the relationship between parental attachment and the psychological well-being of adolescents residing in an Islamic boarding school in West Java. A total of 313 participants, aged 11-18, were included in this supervised online survey, comprising 133 boys and 180 girls. Data analysis was conducted using Pearson correlation tests and regression analysis. The findings reveal a significant positive correlation between parental attachment and adolescents' psychological well-being. These results offer valuable insights into the unique context of Islamic boarding schools, carrying significant implications for educators, parents, and policymakers. This association underscores the fundamental role of establishing trust and emotional connections between parents and adolescents, particularly prior to considering enrollment in Islamic boarding schools. Furthermore, these findings hold importance for educators and policymakers in designing policies within Islamic boarding schools that support well-being. Abstrak: Kesejahteraan psikologis remaja telah menjadi perhatian global. Studi cross-sectional ini menyelidiki hubungan antara keterikatan orang tua dan kesejahteraan psikologis remaja yang tinggal di pondok pesantren di Jawa Barat. Sebanyak 313 partisipan berusia 11-18 tahun berpartisipasi dalam survei daring dengan pengawasan, terdiri dari 133 laki-laki dan 180 perempuan. Analisis data dilakukan dengan menggunakan uji korelasi Pearson dan analisis regresi. Hasil temuan menunjukkan adanya korelasi positif yang signifikan antara keterikatan orang tua dan kesejahteraan psikologis remaja. Hasil penelitian ini memberikan wawasan yang berharga, menyoroti konteks unik pesantren, dan membawa implikasi penting bagi pendidik, orang tua, dan pembuat kebijakan. Asosiasi ini menggarisbawahi peran penting dalam membangun kepercayaan dan hubungan emosional antara orang tua dan remaja, terutama sebelum mempertimbangkan pendaftaran di pondok pesantren. Selain itu, temuan ini juga penting bagi pendidik dan pembuat kebijakan dalam merancang kebijakan di pesantren yang mendukung kesejahteraan santri.